2020
DOI: 10.1007/jhep08(2020)013
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-time-order correlator in coupled harmonic oscillators

Abstract: Exponential growth of thermal out-of-time-order correlator (OTOC) is an indicator of a possible gravity dual, and a simple toy quantum model showing the growth is being looked for. We consider a system of two harmonic oscillators coupled nonlinearly with each other, and numerically observe that the thermal OTOC grows exponentially in time. The system is well-known to be classically chaotic, and is a reduction of Yang-Mills-Higgs theory. The exponential growth is certified because the growth exponent (quantum L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 54 publications
3
32
0
Order By: Relevance
“…This was a motivation for the model of[18], and string theory matrix models in similar spirit are found in[47][48][49][50] 4. For related chaos analyses, see[52][53][54] 5.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…This was a motivation for the model of[18], and string theory matrix models in similar spirit are found in[47][48][49][50] 4. For related chaos analyses, see[52][53][54] 5.…”
mentioning
confidence: 74%
“…This could be due to the fact that our analyses are not semiclassical but fully quantum, and/or the fact that the Hilbert space of our system is infinite dimensional. Pinning down the reason would help us when we generalize the analyses to quantum field theories which have much bigger Hilbert spaces, 18 in view of the holographic principle. Numerical investigation of the semiclassical limits of our system, and comparison to the general semiclassical analyses [68], may provide a path to a resolution.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where the subscript T denotes calculation of the expectation value in a heat bath of temperature T = 1 β . Specifically, introducing the microcanonical OTOC c n (t) as the OTOC for a fixed energy eigenstate |n as in [1] c n (t) = − n|[x(t), p(0)] 2 and if the Hamiltonian is of the form 5) it was shown in ref. [1] that this leads to…”
Section: Jhep01(2021)030mentioning
confidence: 99%
“…Early-time exponential growth of OTOCs has been found in a system of non-linearly coupled oscillators [2], which is expected to exhibit quantum chaos. More recently, however, it has been found that OTOCs show exponential growth in systems that do not possess quantum chaos, such as the inverted harmonic oscillator [3,4].…”
Section: Introductionmentioning
confidence: 99%